2014
DOI: 10.1016/j.enbuild.2014.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Thermal performance optimization of hollow clay bricks made up of paper waste

Abstract: a b s t r a c tIn this paper, the thermal behavior of hollow clay bricks made up of paper waste has been studied and their thermal performance has been optimized. On the one hand, both strength and thermal properties of different paper waste concentrations have been obtained by means of laboratory tests. Thermal conductivity of the microporous brick materials with additives produced in this study reduced from 0.68 W/m K to 0.39 W/m K compared with that of the sample without additives. On the other hand, the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
45
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(50 citation statements)
references
References 23 publications
0
45
0
5
Order By: Relevance
“…The thermal performance of bricks depends on the geometry of the brick recesses and the material properties. The differences of thermal conductivity in function of product geometry are described another study by Sutcu et al [10].…”
Section: Introductionmentioning
confidence: 96%
“…The thermal performance of bricks depends on the geometry of the brick recesses and the material properties. The differences of thermal conductivity in function of product geometry are described another study by Sutcu et al [10].…”
Section: Introductionmentioning
confidence: 96%
“…For example, a few studies are conducted to optimize insulation abilities by designing number and place of voids in the brick structure, mostly by finite volume method [9][10][11][12], whereas one study only shows admixtures of heavy clay and industrial waste [13]. Optimization of the most suitable product form and firing temperature, together with heavy clay raw materials chemical composition, trapezoidal membership function is used [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Conducted in New Zealand, where a considerable volume of waste latex paint exists, it was concluded that waste latex paint was a suitable substitute for common admixtures in concrete masonry blockfill, resulting in maintained strength and improved workability. In another study, paper waste was considered as an additive to produce porous and lightweight hollow clay bricks with reduced thermal conductivity and acceptable compressive strength [17].…”
Section: Introductionmentioning
confidence: 99%